Digitization Of The Pangeran Cakrabuana Museum: A Website-Based Cultural Asset Management Information System - Dian Novianti; Freddy Wicaksono (Ann Publisher, 2025)
Background. This research discusses the digitization of the Prince Cakrabuana Museum through the development of a website-based cultural asset management information system. The background of this research is that the accessibility and efficiency of museum information management remain limited in conventional ways, which affects the dissemination of information and public museum promotion. Aims. This research aims to design and implement a website-based information system that supports the processes of cultural asset inventory, collection documentation, and digital museum information delivery. Methods. The research method used is a qualitative descriptive case study, conducted at the Cirebon Regency Culture and Tourism Office. Data collection techniques are carried out through observation, interviews, and documentation during Field Work Practice (PKL) activities. Result. The results of the study show that the developed system can manage cultural asset data more structurally, increase public access to information, and support the digital promotion of the Prince of Cakrabuana Museum. Conclusion. The conclusion of this study shows that the application of a website-based information system can improve the efficiency of museum asset management and public interest in the preservation of cultural heritage.